2019
DOI: 10.35942/ijcab.v3iii.10
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning and Performance of Hospitality Industry in Kenya: A Case Study of Sarova Whitesands Beach Resort and Spa

Abstract: Organizational learning has been viewed by several researchers as a key concept essential for ensuring the survival and continuity of organizations in the ever-changing business environment. Research has revealed the various benefits towards enhanced performance that are accrued through the effective establishment of organizational learning. With this information as a basis, this study sought to determine the relationship between organizational learning and performance of Sarova Whitesands Resort. The general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
0
0
Order By: Relevance
“…Moreover, the VSH dimensions applied in this study as mediators explain the highest level of the variability in HPO. The degree of influence by ECC in optimising hospitality is supported by other research (Bani-Melhem, 2018; Mak’Anyengo and Maina, 2019).…”
Section: Managerial Implicationssupporting
confidence: 53%
“…Moreover, the VSH dimensions applied in this study as mediators explain the highest level of the variability in HPO. The degree of influence by ECC in optimising hospitality is supported by other research (Bani-Melhem, 2018; Mak’Anyengo and Maina, 2019).…”
Section: Managerial Implicationssupporting
confidence: 53%
“…Makabila et al (2017) found that organizational learning had a positive and significant effect on competitive advantage in state corporations in Kenya. Several other studies found a positive relationship between learning orientation and firm performance (Hussain et al 2017;Nair, 2019;Mak'Anyengo & Maina, 2019).…”
Section: Discussionmentioning
confidence: 88%